Acesso das pessoas aos serviços de telefonia em Senador Canedo - Goiás - Dib Filho, João (2019)
Telephony services play a fundamental role in the realization of communication, which is mainly in the current context, including the globalization and diffusion of the technical-scientific-informative means that becomes a factor of (in) socioeconomic exclusion. In this sense, this is the general objective of analyzing or accessing telephone services by the population of the city of Senador Canedo. Specifically, try to identify the distribution of telephony networks and services in the urban space, focusing on fixed telephony. On the other hand, try to verify the municipal legislation regarding public telephone services in several spheres and to address the socio-spatial segregation of the low income population. The development of this study is justified by the fact that Senador Canedo, belonging to the Goiânia Metropolitan Region, stands out in terms of growth, is an industrial hub and, because of the desperation or interest of the telephone operators. The choice of study areas in the intraurban space was based on differences in the socioeconomic profile of the population. In this sense, the study was conducted in three areas: Bairro Jardim Todos os Santos, which is in the central area; Boa Vista II Neighborhood, Boa Esperança Neighborhood and Jardim do Lago Neighborhood, an attraction north of the Center; and Aracy Amaral neighborhood south of downtown. Methodologically, for the development of the gifts, these items were retrieved in books, academic works, among other bibliographies pertinent to the theme, as well as legal instruments, from federal laws and norms to municipalities, especially the Municipal Master Plan. Allied to the cabinet study, performed as on-site presentations, interviews and data collection. It was found that the low-income population, located in the peripheral neighborhoods, Aracy Amaral neighborhood, Boa Esperança neighborhood and Jardim do Lago neighborhood, do not have access to fixed telephone networks, while in Jardim Todos os Santos neighborhood, where the population of Higher purchasing power is present two operators, evidence that the low-income population is excluded from the basic technological infrastructure, which is allowed to connect, communicate and innovate. In addition, it has been proven that operators do not provide quality service, do not provide all accessibility opportunities